2004
DOI: 10.1021/ol049129u
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Dependent Diastereoselectivities in Reductions of β-Hydroxyketones by SmI2

Abstract: The reductions of a series of beta-hydroxyketones by SmI(2) were examined in THF, DME, and CH(3)CN using methanol as a proton source. Reductions in THF and DME typically lead to the syn diastereomer with DME providing higher diastereoselectivities. Reductions in CH(3)CN provided the anti diastereomer predominantly. This study reveals that solvation plays an important role in substrate reduction by SmI(2). [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…This is supported by the seminal work of Hasegawa and Curran showing that some additives and cosolvents work better in one solvent than another 31 and by more recent work in our group showing that the affinity of alcohols is solvent dependent and that the degree of coordination between a proton donor and Sm(II) can alter the stereochemical outcome of the reactions as well. 3 The molecular basis for solvation effects and the use of these mechanistic studies for the development of selective protocols are currently being explored in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by the seminal work of Hasegawa and Curran showing that some additives and cosolvents work better in one solvent than another 31 and by more recent work in our group showing that the affinity of alcohols is solvent dependent and that the degree of coordination between a proton donor and Sm(II) can alter the stereochemical outcome of the reactions as well. 3 The molecular basis for solvation effects and the use of these mechanistic studies for the development of selective protocols are currently being explored in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments showed that the affinity of the additives was of the order DG > DGME > DGDE, and this indicates that the replacement of a hydroxy hydrogen with a methyl group alters the affinity of the additive for Sm(II). 3 ]I 2 showed that the first two ligands have shorter samarium-oxygen contacts than the third, suggesting that the latter has a lower affinity. Furthermore, the replacement of a hydroxy hydrogen with a methyl group leads to a longer samariumoxygen bond, and the replacement of both hydroxy hydrogen atoms with methyl groups decreases the affinity to such an extent that only two ligands can coordinate to Sm(II), leaving iodides bound to the inner sphere.…”
Section: Scheme 5 First Two Steps In the Reduction Of Acetophenone Bymentioning
confidence: 99%
“…[7,15] More recent work has shown that changes in solvent have a large impact on the interaction of additives with Sm II leading to significant changes in the physical properties and reactivity of the reductant. [16] These findings suggest that the propensity for coordination between competing additives and solvents significantly alters the stability and reactivity of Sm II .…”
Section: Discussionmentioning
confidence: 99%
“…The changes in absorption maxima and relative intensity of the absorption bands in each solvent clearly show that each SmI 2 solvate is unique. [7] Although the synthesis of SmI 2 in alcohols may appear somewhat surprising, recent work in our group has shown that SmI 2 is relatively stable even in the presence of high concentrations of water and glycols. [8,9] Table 1 contains the concentrations (as determined by iodometric titration), λ max , and yields for the synthesis of SmI 2 in each solvent.…”
Section: Generation Of Smimentioning
confidence: 99%
See 1 more Smart Citation